2021
DOI: 10.1172/jci142148
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic loss-of-function variants in PLD1 cause congenital right-sided cardiac valve defects and neonatal cardiomyopathy

Abstract: Congenital heart disease is the most common type of birth defect, accounting for one-third of all congenital anomalies. Using whole-exome sequencing of 2718 patients with congenital heart disease and a search in GeneMatcher, we identified 30 patients from 21 unrelated families of different ancestries with biallelic phospholipase D1 (PLD1) variants who presented predominantly with congenital cardiac valve defects. We also associated recessive PLD1 variants with isolated neonatal cardiomyopathy. Furthermore, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 45 publications
(70 reference statements)
1
18
0
Order By: Relevance
“…14 In 2021, a study reported 21 unrelated families from various ancestries with biallelic PLD1 variants who presented predominantly with congenital cardiac valve defects. 35 The majority of the variants in the 21 cases were located at the HKD1 and HKD2 domain. In our study, the compound heterozygous variants in Family A, I378fs and R391C, were also located at the HKD1 domain.…”
Section: Discussionmentioning
confidence: 98%
“…14 In 2021, a study reported 21 unrelated families from various ancestries with biallelic PLD1 variants who presented predominantly with congenital cardiac valve defects. 35 The majority of the variants in the 21 cases were located at the HKD1 and HKD2 domain. In our study, the compound heterozygous variants in Family A, I378fs and R391C, were also located at the HKD1 domain.…”
Section: Discussionmentioning
confidence: 98%
“…Both the patients in this study had congenital heart defects (CHDs) mainly on the right side. Previously, recessive variants of PLD1 (phospholipase D1; MIM* 602382) were reported to be associated with right‐sided congenital cardiac valve defects (Ta‐Shma et al, 2017), and recently, Lahrouchi et al confirmed that biallelic loss‐of‐function (LOF) variants of PLD1 caused the right‐sided congenital cardiac valve defects (Lahrouchi et al, 2021). PLD1 is a signal transduction enzyme that hydrolyzes the membrane lipid phosphatidylcholine to generate a second messenger.…”
Section: Discussuonmentioning
confidence: 99%
“…PLD1 is a signal transduction enzyme that hydrolyzes the membrane lipid phosphatidylcholine to generate a second messenger. It is reported that the patients carrying biallelic LOF variants had reduced enzymatic activity (lower than 25%) compared with that of individuals having wild‐type alleles (Lahrouchi et al, 2021). It was also noted that the LOF of PLD1 leads to a suppression of TGF‐β and sonic hedgehog signaling, which might induce arterial pole defects in the developing heart.…”
Section: Discussuonmentioning
confidence: 99%
“…Genetic defects responsible for CHD include aneuploidy (presence of an additional chromosome, absence of a chromosome, or deletion/duplication of one arm of a chromosome), copy number variation (deletion or duplication of a segment of a chromosome), and genetic mutations [ 44 , 45 , 46 ]. To date, pathogenic mutations in over 100 genes have been involved in the occurrence of CHD, of which most encode cardiac transcription factors, cell adhesion molecules, signaling pathway proteins, and cardiac structural proteins essential for cardiovascular morphogenesis [ 44 , 45 , 46 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. However, CHD is of pronounced genetic heterogeneity, and the genetic determinants causative for CHD in a significant proportion of cases remain to be identified.…”
Section: Introductionmentioning
confidence: 99%